The risk of venous thromboembolism in adult patients with diffuse glioma: a nationwide population-based study - Frederik R. Hovman; Frantz R. Poulsen; Steinbjørn Hansen; Rikke H. Dahlrot (Acta Oncologica)
Background and purpose: Venous thromboembolism (VTE) is a cause of increased morbidity and risk of death. Studies report VTE in up to 30% of glioma patients but the results vary. The VTE risk is relevant when evaluating prophylaxis to avoid unnecessary bleeding or overdiagnosis. This study examines the VTE incidence in patients with glioma WHO grade 2–4, and when VTE occurred, risk factors, and overall survival (OS) for patients with WHO grade 4.